INTER-GENERATIONAL CONFLICTS IN CONSUMPTION PATTERNS OF BRITISH INDIANS AND ITS IMPLICATION FOR MARKETERS - bhatia, shreya (2006)
This research is an introductory study of the acculturation, assimilation and ethnicity of first, second and third generation Asian Indians. It considers the affects of acculturation and assimilation on the consumption patterns of each generation of Asian Indians in Britain, and aims to highlight some of the conflicts in consumption patterns of each generation in relation to their values, identities and choices. This research explores already existing propositions on acculturation and assimilation with a view to expand our understanding of Asian Indians living in Britain in todays age. This paper conceptualizes the acculturation and ethnicity of the previous generations through previous models developed in the course of primary research. We discuss the results under the areas of Acculturation and Assimilation on the Consumption Choices of Asian Indians, and finally discuss the implications of this research on the scope of Ethnic Marketing.